Mirror tracing's bilateral transfer patterns: investigating transfer between hemispheres and the function of motor imagery - Azhari, Mohamad Nizam Shah; Abd Rahim, Muhammad Nur Ariff; Roslan, Nurul Ain Shafikah; Mohamed, Muhamad Noor; Hidayat, Yusuf; Rahmat, Alit (Faculty of Sports Science and Recreation, 2024)
The present study was conducted to investigate bilateral transfer (BT) in mirror tracing tasks. The objective of the present study is to describe the phenomenon where motor skill acquisition on one side of the body influences performance on the opposite side. Here, we explore the direction and type of BT, focusing on interhemispheric transfer during mirror tracing. Purposive sampling ensured participants (N=20) with diverse motor skills traced predefined paths with both dominant and non-dominant hands. The study aimed to link BT to the mirror neuron system, suggesting improved non-dominant side performance after dominant side training. Additionally, it positions itself for a future systematic review and meta-analysis to evaluate the overall effectiveness of Motor Imagery Training (MIT) in inducing BT effects. The results revealed a statistically significant effect of the trial on time and error value to complete the task (Wilks' Lambda = 0.531, F (3, 17) = 5.008, p < 0.05, η²partial = 0.469) for time and (Wilks' Lambda = 0.607, F (3, 17) = 3.67, p < 0.05, η²partial = 0.393) for error value. It can be concluded that a spectrum of individual responses was present, with some participants exhibiting consistent, symmetrical transfer and others demonstrating asymmetrical transfer characterized by fluctuations in improvement. This study emphasizes the need for tailored interventions based on individual BT patterns and calls for further research on refining strategies for skill acquisition between hands.